2D linear friction weld modelling of a Ti-6Al-4V T-joint - Lee, Lucie Alexandra; McAndrew, Anthony; Buhr, Clement; Beamish, K. A.; Colegrove, Paul A. (Technological Educational Institute of Eastern Macedonia and Thrace, 2015)
Most examples of linear friction weld process models have focused on joining two identically shaped workpieces. This article reports on the development of a 2D model, using the DEFORM finite element package, to investigate the joining of a rectangular Ti-6Al-4V workpiece to a plate of the same material. The work focuses on how this geometry affects the material flow, thermal fields and interface contaminant removal. The results showed that the material flow and thermal fields were not even across the two workpieces. This resulted in more material expulsion being required to remove the interface contaminants from the weld line when compared to joining two identically shaped workpieces. The model also showed that the flash curves away from the weld due to the rectangular upstand "burrowing" into the base plate.Understanding these critical relationships between the geometry and process outputs is crucial for further industrial implementation of the LFW process.
Keywords: Linear friction welding; Finite element analysis; Titanium; Additive manufacture; Material flow; Flash formation; Contaminant removal; Thermal analysis